Van Gogh in acrylics - Sanders, Michael , 1950- (Ready to paint the masters, 2010)
Shows how to reproduce three famous paintings by Vincent Van Gogh, using step by step photographs and instructions and by using acrylic paints. This book contains six tracings for readers to pull out and transfer on to the painting surface and a bonus tracing. It includes two projects that show how to paint in the Van Gogh's style